Δ9-Tetrahydrocannabinol-induced anti-inflammatory responses in adolescent mice switch to proinflammatory in adulthood. Issue 4 (17th April 2014) - Moretti, Sarah; Castelli, Mara; Franchi, Silvia; Raggi, Maria Augusta; Mercolini, Laura; Protti, Michele; Somaini, Lorenzo; Panerai, Alberto E; Sacerdote, Paola
Abstract : Δ9-Tetrahydrocannabinol exposure in adolescent mice induces anti-inflammatory responses; modulation persists into adulthood with immunity switched toward a proinflammatory phenotype. Abstract: Marijuana abuse is prominent among adolescents. Although Δ 9 -THC, one of its main components, has been demonstrated to modulate immunity in adults, little is known about its impact during adolescence on the immune system and the long-lasting effects in adulthood. We demonstrate that 10 days of Δ 9 -THC treatment induced a similar alteration of macrophage and splenocyte cytokines in adolescent and adult mice. Immediately at the end of chronic Δ 9 -THC, a decrease of proinflammatory cytokines IL- 1β and TNF-α and an increase of anti-inflammatory cytokine IL-10 production by macrophages were present as protein and mRNA in adolescent and adult mice. In splenocytes, Δ 9 -THC modulated Th1/Th2 cytokines skewing toward Th2: IFN-γ was reduced, and IL-4 and IL-10 increased. These effects were lost in adult animals, 47 days after the last administration. In contrast, in adult animals treated as adolescents, a perturbation of immune responses, although in an opposite direction, was present. In adults treated as adolescents, a proinflammatory macrophage phenotype was observed (IL-1β and TNF-α were elevated; IL-10 decreased), and the production of Th cytokines was blunted. IgM titers were also reduced. Corticosterone concentrations indicate a long-lasting dysregulation of HPA in adolescent mice. We measured blood concentrations of Δ 9 -THC and its metabolites, showing that Δ 9 -THC plasma levels in our mice are in the order of those achieved in human heavy smokers. Our data demonstrate that Δ 9 -THC in adolescent mice triggers immune dysfunctions that last long after the end of abuse, switching the murine immune system to proinflammatory status in adulthood.